KAJIAN PARAMETER MARSHALL DENGAN MENGGUNAKAN AGREGAT KASAR (DAUR ULANG) MSE WALL (CORNER STONE) PADA CAMPURAN ASPAL AC-BC - Aziz, Mohamad Abdul; Rosyad, Farlin (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Roads function to connect one region to another to share needs, both in economic, social, cultural, governmental and so on. In implementing the road pavement structure, special considerations need to be taken in planning the mixture of coarse aggregate (course aggergate) and fine aggregate (fire aggergate) and filler. One type of pavement layer used in Indonesia is (Laston) asphalt concrete layer mixture. Asphalt Concrete Layer (LASTON) is a layer in road construction consisting of coarse aggregate, fine aggregate, filler and hard asphalt, which are mixed, spread and compacted hot at a certain temperature. The purpose of conducting this research is to determine the effect of using MSE Wall (Corner Stone) Coarse Aggregate (Corner Stone) as an AC BC Asphalt Mixture on Marshall Parameters. This type of research is experimental research, the results of research on the Asphalt Concrete-Wearing Course (AC-WC) mixture with concrete fragment waste as a substitute for coarse aggregate with grades 0% 25% 50% 75% and 100%. The effect of MSE Wall concrete fragment waste as a substitute for coarse aggregate based on Marshall test parameters shows that the optimum value is at an asphalt content of 5.75% and a concrete fragment waste content of 25%, namely with a Stability value of 1056.4%, a Flow value of 3.24% , VFA 73.61%, VMA 16.37%, VIM 4.32%, and MQ 326.1%.